Biomass Accumulation of Chlorella Zofingiensis G1 Cultures Grown Outdoors in Photobioreactors - Huo, Shuhao; Wang, Zhongming; Zhu, Shunni; Shu, Qing; Zhu, Liandong; Qin, Lei; Zhou, Weizheng; Feng, Pingzhong; Zhu, Feifei; Yuan, Zhenhong; Dong, Renjie (Frontiers in Energy Research, 2018)
The complicated and changeable weather conditions and pest invasion increase difficulties in outdoor microalgae cultivation. In this paper, outdoor microalgae cultivation experiments were investigated in Foshan city, South China. During June and August when the temperature is high, the cooling system-water spray combined shade tarpaulin can effectively reduce the temperature to 4–7°C in the 40 L vertical tubular outdoor photobioreactors. Under 300 mg/L urea and 200 mg/L ammonium bicarbonate conditions, Chlorella zofingiensis G1 had the largest biomass accumulation. Addition of acetic acid to adjust the pH of the medium can effectively improve the C. zofingiensis G1 biomass in the photobioreactor, which was four times more than that only through air ventilation conditions. The biomass accumulation of C. zofingiensis G1 was essentially unchanged during night time.